Morpho-Ecotype Characterization of Superior Local Durian (Durio zibethinus L.) in Jember Regency - Sari, Vega Kartika; Sa'diyah, Halimatus; Basuki, Basuki (Journal of Tropical Biodiversity and Biotechnology, 2024)
Panti and Sumberjambe Districs are known as durian centre in Jember Regency, it is necessary to characterise the main potential superior durian trees. The exploratory investigation was carried out between April - July 2023. Morphological characterisation and Ecological observations including topography, soil type and climate were carried out. Data were analysed in clusters and descriptively. The results showed that 10 local durian accessions from Panti District had 66% similarity. The highest similarity between Montong Belanda and Gendon durians (75%). Ten local durians from Sumberjambe showed 64% similarity. Si Sukun differed significantly, whereas LK 1 and LK 4 shared 85% similarity.